The occasionally accurate annals of football : the NFL's greatest players, plays, scandals, and screw-ups (plus stuff we totally made up) - Patrick, Dan, 1957-; Cohen, Joel H. (Television writer) (BenBella Books, Inc., 2023)
"The Occasionally Accurate Annals of Football is a love letter to America's favorite game, full of highlights, history, great plays and players, scandals, Super Bowls, and a series of lies, idiotic theories, baseless conspiracies, a diet that may kill you and, of course, a poorly-written haiku"--